Translation and Testing of the Verbal and Social Interaction for Nursing Students Questionnaire in Thailand - Chaimongkol, Nujjaree; Hengudomsub, Pornpat; Sarapat, Photjanart; Lakthong, Sawitree (Pacific Rim International Journal of Nursing Research, 2020)
A measure to assess the verbal and social caring interactions, and communication skills of nursing students is important as a baseline in nursing education, but until this study, there was no instrument available in Thailand. We translated the revised Verbal and Social Interaction for Nursing Students questionnaire into Thai, using a back-translation method. Participants included 158 consenting senior nursing students at an Eastern Thailand university who were caring for people with psychiatric-mental health problems. Internal consistency reliability and construct validity were tested, using descriptive statistics, confirmatory factor analysis, correlation coefficients, and Cronbach’s alpha for internal reliability. Results revealed that the Verbal and Social Interaction for Nursing Students (Thai) version was well-understood by the nursing students. The translated scale yielded acceptable reliability values ranging from 0.88-0.93. The measurement models were modified through modification indices and the final model fit the data, thus confirming construct validity. The translated scale was evidenced to be a valid and reliable instrument. Nurse educators in Thailand may use this scale to assess the competency of nursing students interacting with clients requiring not only psychiatric-mental health care but routine care as well. We recommend further testing of the scale with different groups of nursing students across Thailand.